Microbial ecology of the oceans - Gasol, Josep M., 1962-; Kirchman, David L. (Wiley Blackwell, 2018)
The third edition of Microbial Ecology of the Oceans features new topics, as well as different approaches to subjects dealt with in previous editions. The book starts out with a general introduction to the changes in the field, as well as looking at the prospects for the coming years. Chapters cover ecology, diversity, and function of microbes, and of microbial genes in the ocean. The biology and ecology of some model organisms, and how we can model the whole of the marine microbes, are dealt with, and some of the trophic roles that have changed in the last years are discussed. Finally, the role of microbes in the oceanic P cycle are presented.